Thermodynamics of Phase Equilibria in Food Engineering - Pereira, Camila Gambini (Academic Press, 2019)
Thermodynamics of Phase Equilibria in Food Engineering is the definitive book on thermodynamics of equilibrium applied to food engineering. Food is a complex matrix consisting of different groups of compounds divided into macronutrients (lipids, carbohydrates, and proteins), and micronutrients (vitamins, minerals, and phytochemicals). The quality characteristics of food products associated with the sensorial, physical and microbiological attributes are directly related to the thermodynamic properties of specific compounds and complexes that are formed during processing or by the action of diverse interventions, such as the environment, biochemical reactions, and others. In addition, in obtaining bioactive substances using separation processes, the knowledge of phase equilibria of food systems is essential to provide an efficient separation, with a low cost in the process and high selectivity in the recovery of the desired component. This book combines theory and application of phase equilibria data of systems containing food compounds to help food engineers and researchers to solve complex problems found in food processing. It provides support to researchers from academia and industry to better understand the behavior of food materials in the face of processing effects, and to develop ways to improve the quality of the food products.